Impact of Foreign Direct Investment and Tax Revenues on the Economic Growth of Five Asean Countries - Fibria Anggraini Puji Lestari (Institute of Advanced Knowledge and Science, 2026)
This study was conducted to examine the impact of domestic foreign investment and tax revenues in ASEAN countries, in particular Indonesia, Malaysia, the Philippines, Thailand and Vietnam, between 2014 and 2024. This study uses secondary data on foreign direct investment (FDI), independent tax variables, and economic growth. According to the study, foreign direct investment and income tax variables affect the economic growth of five ASEAN countries, namely Indonesia, Malaysia, Thailand, the Philippines and Vietnam, both simultaneously and partially. The governments of each country have taken various measures to promote economic growth, including cutting red tape, tax reform, improving business, ensuring financial security and stability, allowing foreign direct investment to come in and increasing tax revenues. So, it can be used to finance development and influence the economic growth of each ASEAN country.